2013
DOI: 10.3390/ijms14022862
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and in Vivo Evaluation of Lactoferrin-Conjugated Liposomes as a Novel Carrier to Improve the Brain Delivery

Abstract: In this study, lactoferrin-conjugated PEGylated liposomes (PL), a potential drug carrier for brain delivery, was loaded with radioisotope complex, 99mTc labeled N,N-bis(2-mercaptoethyl)-N′,N′-diethylethylenediamine (99mTc-BMEDA) for in vitro and in vivo evaluations. The hydrophilicity of liposomes was enhanced by PEGylation which was not an ideal brain delivery system for crossing the blood brain barrier (BBB). With the modification of a brain-targeting ligand, lactoferrin (Lf), the PEGylated liposome (PL) mig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(29 citation statements)
references
References 32 publications
1
28
0
Order By: Relevance
“…Other studies using Lf-bearing drug delivery systems have also reported an increase of the drug delivery to the brain after intravenous injection, however associated with an increase of the amount of drug delivered to non-specific organs. For example, the administration of Lf-bearing PEG-liposomes encapsulating coumarin-6 resulted in a 1.4-fold increase in the brain uptake of the drug compared to that observed with PEG-liposomes, but non-specific uptake in spleen also increased [26]. In another study, Lf -bearing -cyclodextrin nanocarrier increased the brain uptake of the delivery system by 3.5-fold compared to the non-targeted carrier [27].…”
Section: In Vivo Studymentioning
confidence: 96%
“…Other studies using Lf-bearing drug delivery systems have also reported an increase of the drug delivery to the brain after intravenous injection, however associated with an increase of the amount of drug delivered to non-specific organs. For example, the administration of Lf-bearing PEG-liposomes encapsulating coumarin-6 resulted in a 1.4-fold increase in the brain uptake of the drug compared to that observed with PEG-liposomes, but non-specific uptake in spleen also increased [26]. In another study, Lf -bearing -cyclodextrin nanocarrier increased the brain uptake of the delivery system by 3.5-fold compared to the non-targeted carrier [27].…”
Section: In Vivo Studymentioning
confidence: 96%
“…Another peptide (tyrosine-3-octreotide) conjugated liposomes were also reported to generate low to moderate tumor uptake (< 2.5 %ID/g) in xenografted mice (76). Also, synthesis of lactoferrin-conjugated PEGylated liposomes loaded with radioisotope complex, 99m Tc-labeled N,N-bis(2-mercaptoethyl)-N',N'-diethylethylenediamine ( 99m Tc-BMEDA) for SPECT-IGDD to brain was reported by Huang et al (77). In vivo SPECT imaging and biodistribution studies revealed that lactoferrin conjugated PEGylated liposome showed two-fold higher brain uptake than control PEGylated liposome.…”
Section: Carriers For Spect-igddmentioning
confidence: 99%
“…Conjugation with antibodies makes liposomes more recognizable by ECs. 98 To deliver PEG-treated liposomes to the brain, the liposomes undergo an additional modification involving conjugation of monoclonal antibodies to glia, transferrin receptors (OX-26), lactoferrin receptors, 99 low-density lipoprotein (LDL) receptors, 100 or insulin receptors. 101 Evidence suggests that conjugation of a liposome with diphtheria toxin receptor (Heparin binding [HB]-EGF) also represents a promising method for drug delivery across the BBB.…”
Section: Liposomesmentioning
confidence: 99%